Synthesis, antiprotozoal activity and cytotoxicity in U-937 macrophages of triclosan–hydrazone hybrids (2017)
ABSTRACT: The synthesis and biological activities (cytotoxicity, leishmanicidal, and trypanocidal) of 11 triclosan–hydrazone hybrids are described herein. The structure of the products was elucidated by spectral data (NMR, IR) and mass spectrometric analyses. The synthesized compounds were evaluated against amastigotes forms of L. (V) panamensis, which is the most prevalent Leish-mania species in Colombia, and against Trypanosoma cruzi, which is the major pathogenic species to Chagas disease in humans. In addition, the cytotoxic activity of the synthesized compounds was evaluated against human U- 937 macrophages. Hydrazone hybrids were obtained as Esynperiplanar and E-antiperiplanar conformers. Nine of them were active against L. (V) panamensis (5a–5d, 5f–5j) and eight of them against T. cruzi (5a, 5c, 5d, 5f–5j), with EC50 values lower than 40 μM. The compounds 5c, 5e, and 5h exhibit the best selectivity index against both L. (V) panamensis and T. cruzi, with values ranging from 5.90 to 16.55, thus showing potential as starting compounds for the eventual development of drugs against these parasites. The presence of hydroxy or methoxy groups in positions 2 and 4 of the aromatic ring of the benzylidene moiety increases both activity and cytotoxicity. There is no clear relationship between the antiprotozoal activity and the methylation pattern of the hydroxy groups, since in some cases methylation decreases the activity (5d vs. 5g) while in other cases the activity is increased (5c vs. 5f and 5i vs. 5j).